2008
DOI: 10.1097/rti.0b013e31815a662d
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-related Kaposi Sarcoma of the Lung Presenting With a “Crazy-paving” Pattern on High-resolution CT

Abstract: Kaposi sarcoma (KS) is a fulminate and disseminated form of acquired immunodeficiency syndrome (AIDS)-defining neoplasm, usually presenting pulmonary involvement. We report a 40-year-old woman with AIDS and biopsy-proven KS showing unusual high-resolution computed tomography (HRCT) findings. HRCT showed areas of ground-glass attenuation with superimposed septal thickening ("crazy-paving" pattern). CT-pathologic correlation revealed that crazy-paving pattern in this case was due to accompanying pulmonary edema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…The confluence of the lesions leads to progressive air-space consolidation, possibly with a component of airway obstruction. Other HRCT scan findings are interlobular septal thickening, usually preserving the lobular architecture and simulating carcinomatous lymphangitis; large parenchymal nodules with irregular, poorly defined, and spiculated borders (Figure 3 ), some of them with a perinodular ground glass halo sign and air bronchograms; fissural nodularity; ground-glass opacities (Figure 4 ); mediastinal adenopathies; and pleural effusions [ 5 , 11 , 20 , 21 , 27 , 28 , 30 - 32 ] (Figure 5 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The confluence of the lesions leads to progressive air-space consolidation, possibly with a component of airway obstruction. Other HRCT scan findings are interlobular septal thickening, usually preserving the lobular architecture and simulating carcinomatous lymphangitis; large parenchymal nodules with irregular, poorly defined, and spiculated borders (Figure 3 ), some of them with a perinodular ground glass halo sign and air bronchograms; fissural nodularity; ground-glass opacities (Figure 4 ); mediastinal adenopathies; and pleural effusions [ 5 , 11 , 20 , 21 , 27 , 28 , 30 - 32 ] (Figure 5 ).…”
Section: Reviewmentioning
confidence: 99%
“…Silva Filho et al [ 32 ] reported the association of the "crazy-paving" pattern with peribronchovascular thickening in patients with pulmonary KS. This pathological correlation demonstrated that the areas of ground-glass attenuation represented edema and filling of air spaces with blood, and that the interlobular septal thickening was related to the infiltration of the interlobular septa by neoplastic cells (Figure 9 ).…”
Section: Reviewmentioning
confidence: 99%
“…1) [4]. The crazypaving pattern was initially described as a pathognomonic sign of alveolar proteinosis; however, nowadays, this pattern has been reported in a variety of acute and chronic diseases as summarised in Table 1 [2,[5][6][7][8]. The purpose of this paper is to illustrate different diseases showing a crazypaving pattern.…”
Section: Introductionmentioning
confidence: 97%
“…In most patients, the presence of typical nodules in CT and perihilar distribution of the aforementioned abnormalities justify KS being considered together with other thoracic affections in AIDS. 2,15,[18][19][20]25,[27][28][29][30][31][32] conclusion The diagnosis of pulmonary KS is still a challenge, especially due to the occurrence of other opportunistic diseases that may also occur concurrently. Therefore, suspecting this diagnosis based on clinical and laboratory manifestations, and even more with CT findings, is fundamental, especially in patients who already have the cutaneous form of the disease, so that proper treatment can be initiated as soon as possible.…”
Section: Introductionmentioning
confidence: 99%